2016
DOI: 10.1007/s11481-016-9698-1
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Targeted Drug Delivery Approaches for the Central Nervous System Tumors: The Inspiration of Nanobiotechnology

Abstract: At present, brain tumor is among the most challenging diseases to treat and the therapy is limited by the lack of effective methods to deliver anticancer agents across the blood-brain barrier (BBB). BBB is a selective barrier that separates the circulating blood from the brain extracellular fluid. In its neuroprotective function, BBB prevents the entry of toxins, as well as most of anticancer agents and is the main impediment for brain targeted drug delivery approaches. Nanotechnology-based delivery systems pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 165 publications
0
53
0
Order By: Relevance
“…As an atypical antipsychotic, amisulpride treatment results in larger effect size than first and second generation of antipsychotics with efficacy equal to olanzapine and risperidone in large scale RCT in schizophrenia [63]. A recent meta-analysis of randomized controlled trials to compare 15 antipsychotic drugs versus placebo in acute treatment of schizophrenia showed that amilosulpride ranked second to clozapine in the efficacy measure of standardized mean differences with 95% credible intervals clozapine 0.88, 0.73-1.03; amilosulpride 0.66, 0.53-0.78.…”
Section: Epigenetics Footprints and Curcuminmentioning
confidence: 99%
See 1 more Smart Citation
“…As an atypical antipsychotic, amisulpride treatment results in larger effect size than first and second generation of antipsychotics with efficacy equal to olanzapine and risperidone in large scale RCT in schizophrenia [63]. A recent meta-analysis of randomized controlled trials to compare 15 antipsychotic drugs versus placebo in acute treatment of schizophrenia showed that amilosulpride ranked second to clozapine in the efficacy measure of standardized mean differences with 95% credible intervals clozapine 0.88, 0.73-1.03; amilosulpride 0.66, 0.53-0.78.…”
Section: Epigenetics Footprints and Curcuminmentioning
confidence: 99%
“…On the other hand, amisulpride behaves as a selective antagonist at the serotonin-receptor subtype 7: (5HT-7) mediating its likely procognitive action [62]. The pharmacological profile of amisulpride raises the intriguing hypothesis whether complex interactions at the D2/D3 and 5-HT-7 receptors reflect altered expression of D2/ D3 and 5HT (7) genes because of potent HDAC inhibition.As an atypical antipsychotic, amisulpride treatment results in larger effect size than first and second generation of antipsychotics with efficacy equal to olanzapine and risperidone in large scale RCT in schizophrenia [63]. A recent meta-analysis of randomized controlled trials to compare 15 antipsychotic drugs versus placebo in acute treatment of schizophrenia showed that amilosulpride ranked second to clozapine in the efficacy measure of standardized mean differences with 95% credible intervals clozapine 0.88, 0.73-1.03; amilosulpride 0.66, 0.53-0.78.…”
mentioning
confidence: 99%
“…Nanocarriers (NCs), such as liposomes, hydrogels, nanoparticles, micelles, fibers, and dendrimers, provide several advantages in delivery applications and have been extensively applied to enhance the therapeutic efficacy of drugs [1][2][3][4]. However, the major challenges in NC applications are to transport the therapeutics to the target site without significant degradation, avoid rapid phagocytic clearance, prolonging the circulation time, insufficient targeting, and limited ability to cross biological barriers such as the blood-brain barrier [1][2][3][4].…”
Section: Circulatory Cells As Drug Carriersmentioning
confidence: 99%
“…However, the major challenges in NC applications are to transport the therapeutics to the target site without significant degradation, avoid rapid phagocytic clearance, prolonging the circulation time, insufficient targeting, and limited ability to cross biological barriers such as the blood-brain barrier [1][2][3][4]. Thus, alternative drug delivery approaches are desirable.…”
Section: Circulatory Cells As Drug Carriersmentioning
confidence: 99%
“…The failure of vast majority of novel and current experiential therapeutics to reach/target the brain at a reasonable effective dose remains a major challenge. Despite great stride in understanding of the brain biology, from cellular to behavioral levels, the advances in basic science have not yet been fully developed in an interdisciplinary way, and a definitive translation from bench to bedside is still uncertain [6]. The scope of current communication focuses current challenges in brain-drug delivery, and significance of nanomedicine in crossing BBB, their downside and future prospects are also discussed.…”
Section: Introductionmentioning
confidence: 99%